ҚУБЛА АРАЛ БОЙЫ ЭТНОМӘДЕНИЯТЫНЫҢ ДӘСТҮРИЙЛИГИ МӘСЕЛЕСИ - Досмағанбетов, С.; Юсупов, О.; Қайыпназаров, А. (ILIM hám JÁMIYET, 2017)
This article deals with the analysis of the identity of ethno-culture “symbiosis”, ethno-tradition of two ethnoses-Kazakhs and Karakalpaks on the basis of the latest scientific literature in ethnography and ethno-folklore materials. These two, ethnoses have been living for many centuries in the down streams and deltas of Amudarya river, as well as around the Aral sea.